Mediating role of resistance in relationships between organizational culture, change, innovation, and organizational effectiveness in commercial banking sector of Pakistan - Naveed, Rana Tahir (2017)
The purpose of the current study is to examine the mediating role of organizational resistance in the relationship between organizational culture; organizational change and organizational innovation with organizational effectiveness of commercial banking sector in Pakistan. A total of 380 bankers from six banks (UBL; ABL; MCB; HBL and BAF) participated in the current study. A survey was conducted and questionnaires were used to collect data from bankers. SPSS, AMOS and PROCESS statistical software were used to analyze the data collected. The results provide details of descriptive statistics data. 510 sets of questionnaires were distributed, but only 380 sets were used for further analysis. Confirmatory factor analysis (CFA) is used for every variable conducted to verify the loading factor of each and every item. The measurement model and structural model indicate that the items in the current structural model fit indices, convergent validity, average variance extracted (AVE), composite reliability (CR) and validity. The loading factor of every variable reaches the threshold value, AVE values (5.55, 2.09, 0.92, 2.52, and 2.26). The CR values are as follow (0.98, 0.98, 0.94, 0.97, and 0.96) and the overall structural model can be considered as an excellent model because it fits the indices. The seven hypotheses on direct relationships between independent variables to mediator and mediator to dependent variables are significant (p < 0.05). Consequently, all hypotheses on direct relationships are supported. Moreover, the results show that organizational resistance is significant and partially mediate the relationships between organizational culture and organizational effectiveness. The results also indicate organizational resistance is significant and partially mediate the relationships between organizational change and organizational effectiveness. Similarly, organizational resistance is significant and partially mediate the relationship between organizational innovation and organizational effectiveness. Organizational resistance in the context of studying organizational development, change management and organizational behaviors in the banking sector should be considered as an important factor, which could contribute to understanding, explaining and improving organizational effectiveness of the banking sector. Future researchers could bring new perspectives to management practitioners, organizational development practitioners, business leaders, bankers as well as change agents in the banking sectors. The new perspective should thus consider organizational resistance as an undeniable factor among employees and at the same time it can help them to improve organizational effectiveness and to achieve the desired outcomes.